7 tesla magnetic resonance imaging: A closer look at substantia nigra anatomy in Parkinson's disease. Issue 13 (12th October 2014) - Lehéricy, Stéphane; Bardinet, Eric; Poupon, Cyril; Vidailhet, Marie; François, Chantal
Abstract A hallmark of Parkinson's disease (PD) is the progressive neurodegeneration of dopaminergic neurons in the substantia nigra pars compacta (SNc). Dopaminergic denervation is commonly imaged using radiotracer imaging in target structures such as the striatum. Until recently, imaging made only a modest contribution to detecting neurodegenerative changes in the substantia nigra (SN) directly. Histologically, the SN is subdivided into the ventral pars reticulata and the dorsal pars compacta, which is composed of dopaminergic neurons. In humans, dopaminergic neurons, which are known to accumulate neuromelanin, form clusters of cells (nigrosomes) that penetrate deep into the SN pars reticulata (SNr). The SNr contains higher levels of iron than the SNc in normal subjects. Neuromelanin and T2*‐weighted imaging therefore better detect the SNc and the SNr, respectively. The development of ultra‐high field 7 Tesla (7T) magnetic resonance imaging (MRI) provided the increase in spatial resolution and in contrast that was needed to detect changes in SN morphology. 7T MRI allows visualization of nigrosome‐1 as a hyperintense signal area on T2*‐weighted images in the SNc of healthy subjects and its absence in PD patients, probably because of the loss of melanized neurons and the increase of iron deposition. This review is designed to provide a better understanding of the correspondence between the outlines and subdivisions of the SN detected using different MRI contrasts and the histological organization of the SN. The recent findings obtained at 7T will then be presented in relation to histological knowledge. © 2014 International Parkinson and Movement Disorder Society